Respuesta :

Answer:

[tex]a_{n} = a_{n-1} + 3[/tex] and [tex]a_{1} = -2[/tex]

Step-by-step explanation:

The terms of an arithmetic sequence are given by the formula

[tex]a_{n} = -2 + (n - 1)3 = 3n - 5[/tex]

So, the first term, [tex]a_{1} = 3(1) - 5 = - 2[/tex]

The second term, [tex]a_{2} = 3(2) - 5 = 1[/tex]

The third term, [tex]a_{3} = 3(3) - 5 = 4[/tex]

And the fourth term, [tex]a_{4} = 3(4) - 5 = 7[/tex]

So, from the terms of the A.P. sequence, it is clear that,

[tex]a_{n} = a_{n-1} + 3[/tex] and [tex]a_{1} = -2[/tex]

Therefore, this is the recursive formula of the given arithmetic sequence. (Answer)

ACCESS MORE